A comprehensive retrospective analysis of the COVID-19 pandemic’s impact on Baghdad Province - Zainab Basim Mohammed (International Journal of Medical Toxicology and Legal Medicine, 2024)
In the beginning, the newly discovered pandemic ailment known as coronavirus was only found in Wuhan, China, but then, it has spread to other countries. In Iraq, in particular Baghdad province, reports of incidents of this nature are received on a consistent basis. This study aims to characterization and assessment the state of COVID-19 in Baghdad with regard to confirmed cases,related percent of signs and symptoms with accompanied disease between the years 2020 and the present. According to our findings, cases of COVID-19 are gradually increased until they reach their highest peak in 2021, and then begin to progressively decline. The severity of illness increases with age, more obviously in males (60.2%) than females (39.8%). However, the mild cases of disease were more common (44%) than moderate (35.7%) and severe (20.3%). The most common comorbidity was hypertension (60%) followed by diabetic mellitus (40%) of total patients. Depending on clinical symptoms; anxiety (100%), loss of smell and taste (85.5%), and unresolved fever (70%) were the most common. Hypertension was highly associated with the moderate to severe illness (40.6%) than the mild one (39.2%) followed by diabetes mellitus (28.2%) and cardiovascular disease (20.1%) respectively. Patients with age 51-60 years have an OR of 1.908 (p<0.001), indicating higher odds of having a "moderate to severe" condition. Similarly, individuals aged 61-70 years have an OR of 1.520 (p < 0.001). Our study concludes that people with hypertension and diabetes mellitus are at a higher risk of developing moderate to severe disease, particularly among older adults. The prevalence of moderate to severe illness is significantly higher in individuals aged 51-70 years, with males being more susceptible than females. Hypertension emerges as the most prevalent comorbidity, particularly among patients with more severe symptoms. In Baghdad, COVID-19 is subject to restrictions imposed by government procedures and vaccination requirements. On the other hand, a number of studies from all across the world have found that there is reason to question that the global pandemic has come to an end. All studies discuss the effects of vaccines and other factors such as comorbidities and disease interactions, but the genetic factors and predispositions that have not yet been highlighted, as well as the repercussions that appeared in patients who were vaccinated after a period of time, have not been addressed.